2015
DOI: 10.1111/cen.12738
|View full text |Cite
|
Sign up to set email alerts
|

Higher serum testosterone and dihydrotestosterone, but not oestradiol, are independently associated with favourable indices of lung function in community‐dwelling men

Abstract: Both T and DHT were independently associated with higher FEV1 and FVC in predominantly middle-aged community-dwelling men. Androgens may contribute to, or be biomarkers for, better lung function in men. Further research is needed to clarify whether androgens preserve lung function in ageing men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 38 publications
7
54
0
Order By: Relevance
“…Of note, asthmatic men with low total testosterone levels had lower lung function than asthmatic men with normal testosterone levels-consistent with studies in non-asthmatic populations [18,19]-and total testosterone values in men with severe asthma were lower than those in men with non-severe asthma. These data also suggest a protective effect of androgens on lung function.…”
Section: Background and Significance Regarding Androgens For Patientssupporting
confidence: 81%
“…Of note, asthmatic men with low total testosterone levels had lower lung function than asthmatic men with normal testosterone levels-consistent with studies in non-asthmatic populations [18,19]-and total testosterone values in men with severe asthma were lower than those in men with non-severe asthma. These data also suggest a protective effect of androgens on lung function.…”
Section: Background and Significance Regarding Androgens For Patientssupporting
confidence: 81%
“…20 Recent studies in men also shown that testosterone levels in smokers was higher than non-smokers. 36 These results are also consistent with studies showing the variation of FT levels in healthy adult males. 37 The average levels of SHBG in this study 34.01±1.53 nmol/L.…”
Section: Parwanto Mle Int J Res Med Sci 2017 Aug;5(8):3431-3437supporting
confidence: 91%
“…Testosterone is associated with decreased Th2 and Th1 inflammation in animal models of asthma (8,9). Epidemiologically, androgens are associated with better lung function in large healthy cohorts (10,11) and in disease (12). Increasing circulating levels of adrenal and gonadal androgens in males and females during adolescence are believed to be associated with improving asthma during adolescence (12), and gonadal androgens in particular may be associated with gender-based differences in asthma incidence and severity in adulthood (12,(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Androgens inhibit human airway smooth muscle and fibroblast proliferation (4-6), promote airway smooth muscle relaxation (7), and inhibit both Th2 and Th1 inflammation in animal models of asthma (8,9). Androgens are associated with better lung function in large healthy cohorts (10,11) and in asthma (12). Increasing circulating…”
mentioning
confidence: 99%